As configurações da situação de encarceramento de idosos em Porto Alegre/RS - Wacheleski, Nadia Regina (2015)
This study aims at learning the configurations regarding the situation of elderly in prison by considering as research setting the Central Prison of Porto Alegre/RS. It is a qualitative research about the phenomenon studied from a triangle approach of different theoretical lines and distinct techniques of social research. The epistemological construction of the theoretical study about this issue is consubstantiated in the bibliographic review and documental research. Besides it is founded in the referrals of the historic and dialectic materialism, of the critical criminology and of the social gerontology. This work counted on the collaborative participation, by free and spontaneous will, of ten prisoned elderly over sixty years old. The elderly reported their experience in the prison upon interviews of oral thematic history which was the main technique utilized in the collection process that gathered stories and not data. The instrument that made their application viable was the script of thematic oral history, organized within thematic axes with the objective of constructing an ontological apprehension of the reality. The technique of participative observation with the resource of the field diary allowed the registration of notes about the day-to-day life and the research development that contributed in a significant way for the analysis of the interconnections and the multiple determinants involved in the elderly imprisonment. The research provided more visibility to the social experiences of elderly in prison by means of stories that are presented partially and analyzed from their intercession points. Thus, the present study aims at contributing for the qualification of criminal and penitentiary public policies that pay attention to the violation of human rights of imprisoned elderly. In addition, it unveils the penalty overcharges experienced by the elderly in the penal institution, the crystallization of their specificities, their needs that disappeared under the prison dynamics and the main difficulties they face in this situation.